Odpowiedź :
½×(2ײ-4×+8)=
x³-2x²+4x
3(3×+2y)-2(2×+3y)=
9x+6y-(4x+6y)=
9x+6y-4x-6y=
5x
√6(√2+√3)=
√12 + √18=
2√3 + 3√√2
x³-2x²+4x
3(3×+2y)-2(2×+3y)=
9x+6y-(4x+6y)=
9x+6y-4x-6y=
5x
√6(√2+√3)=
√12 + √18=
2√3 + 3√√2
½×(2ײ-4×+8)=
x³-2x²+4x
3(3×+2y)-2(2×+3y)=
9x+6y-(4x+6y)=
9x+6y-4x-6y=
5x
√6(√2+√3)=
√12 + √18=
2√3 + 3√√2
x³-2x²+4x
3(3×+2y)-2(2×+3y)=
9x+6y-(4x+6y)=
9x+6y-4x-6y=
5x
√6(√2+√3)=
√12 + √18=
2√3 + 3√√2
½×(2ײ-4×+8)=x^3-2x^2+4x
3(3×+2y)-2(2×+3y)=9x+6y-4x-6y=5x
√6(√2+√3)=√12 + √18 = 2√3 + 3√2
3(3×+2y)-2(2×+3y)=9x+6y-4x-6y=5x
√6(√2+√3)=√12 + √18 = 2√3 + 3√2